2011
DOI: 10.1177/1078155210390254
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin administration in cancer patients with hypercoagulability-related complications and carrying brain metastases: A case series study

Abstract: There is no standard medical approach for the management of patients who require anticoagulant treatment and are suffering from brain MTS. These patients as necessary, might be anticoagulated with LMWH and its dose reduction is to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
2
11
0
1
Order By: Relevance
“…The absence of an effect of low-molecular-weight heparin on rates of intracranial hemorrhage is consistent with the findings of smaller studies, including a case series of 38 patients 15 and a retrospective cohort study of 44 patients with melanoma brain metastases. 7 In the current study, the only covariate that was predictive of hemorrhage was the combined group of renal cell carcinoma and melanoma.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The absence of an effect of low-molecular-weight heparin on rates of intracranial hemorrhage is consistent with the findings of smaller studies, including a case series of 38 patients 15 and a retrospective cohort study of 44 patients with melanoma brain metastases. 7 In the current study, the only covariate that was predictive of hemorrhage was the combined group of renal cell carcinoma and melanoma.…”
Section: Discussionsupporting
confidence: 85%
“…Initial sample size estimates were based on an anticipated rate of intracranial hemorrhage of 7% in the enoxaparin cohort and 2% in the control cohort. 6,7,15 Accordingly, the target analysis was approximately 200 patients treated with enoxaparin and 400 controls (1-sided a of 0.05% and power of 0.85). For the 3 primary bleeding end points, analysis was performed using a competing risk approach to account for death as a competing risk for intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 40 patients, 1 developed a dvt while taking tinzaparin, and 3 developed thromboembolic complications while off tinzaparin 58 . Similar findings from retrospective reviews of bleeding events have been reported elsewhere in patients with central nervous system malignancy receiving prophylactic anticoagulation 71,72 .…”
Section: 55supporting
confidence: 74%
“…In a study with 203 metastatic cancer patients of whom 44 had brain metastases, patients received dalteparin and no increased incidence of a major bleeding episode was observed [130]. In a study by Vitale et al, 26 lung cancer patients with CNS metastases were treated with a LMWH and no patient developed intracranial hemorrhage [131]. Other complications of lung cancer such as hemoptysis should also be taken in consideration.…”
Section: Treatment Of Thrombosismentioning
confidence: 95%